Efficacy of I-131 MIBG Myocardial Scintigraphy for the Differentiation Between Parkinson’s Disease and Multiple System Atrophy - Hussain, Mehmood; Hussain, Fida; Malik, Asad; Khan, Malik Nadeem Azam; Saleem, Zaigham; Rehman, Maryam (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess efficacy of I-131 Metaiodobenzylguanidine Myocardial Scintigraphy for differentiation between Parkinson’s Disease and Multiple System Atrophy. Study Design: Validation Study. Place and Duration of Study: Department of Neurology, Pakistan Emirates Military Hospital, Rawalpindi Pakistan, from May 2019 to Jan 2022. Methodology: Undiagnosed patients with motor and autonomic symptoms of Parkinsonism were enrolled. I-131 Meta-iodobenzylguanidine Myocardial Scintigraphy was performed and subjects were diagnosed as per early (15 min) and late (4h) heart/mediastinum ratios with washout ratio. At the same time, patients were reviewed for clinical diagnosis using clinical criteria, radiological studies and followed up for 2 years or till definitive clinical diagnosis was formed. Sensitivity and Specifi-city of I-131 Metaiodobenzylguanidine for Diagnosis of Parkinson’s Disease and Multiple System Atrophy was calculated. Results: Out of 79 patients, 48 were diagnosed with Parkinson’s Disease, 15 with Multiple System Atrophy and 16 fell in criteria for other diseases. Early heart/mediastinum, Late heart/mediastinum and washout ratio in Parkinson’s group was 1.53±0.19, 1.39±0.18 and 37.20±17.91, in Multiple System Atrophy was 2.02±0.10, 2.00±0.11 and 11.35±9.46 and in others was 2.36±0.18, 2.41±0.18 and 0.40±22.49 respectively. This revealed a sensitivity and specificity of 83.67% and 76.67% for Parkinson’s Disease and 66.67% and 92.19% for Multiple System Atrophy respectively. Conclusion: I-131 Metaiodobenzylguanidine can be used to help in differential diagnosis of Parkinsonism with autonomic features, with good sensitivity and specificity.